Improving students' problem-solving abilities by using geogebra learning media on three-dimensional material - Ramadiana, Anastasya; Takaendengan, Bertu Rianto; Nurwan, Nurwan; Zakaria, Perry; Usman, Kartin; Yahya, Lailany (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2024)
The COVID-19 pandemic has had an impact on the learning process in schools. For this reason, researchers observed learning at SMA Negeri 1 Gorontalo, it was found that students were still not optimal in solving mathematical problems, especially in formulating steps to solve problems. This research aims to improve students' problem-solving abilities by using GeoGebra on three-dimensional material. The research was carried out at SMA Negeri 1 Gorontalo in class XII IPA 5 from September to October of the 2022/2023 academic year with research subjects totaling 30 students. The research is Classroom Action Research (CAR) using the Kemmis and McTaggart model, which involves the stages of planning, action, observation, and reflection. Data was obtained from observation and written tests. Analysis of observation results was obtained by calculating scores for each aspect criterion observed both on the teacher observation sheet and the student observation sheet, while the written test was analyzed by referring to the minimum completeness criteria. The results of the research show that there is an increase in students' problem-solving abilities in three-dimensional material after taking action using the GeoGebra learning media.